Sensibilidad y especificidad de método ECOFAST como método diagnóstico para pacientes con dengue del Hospital Regional de Loreto 2023 - Lecca Reyes, Luis Paul Anatoly (2024)
GENERAL OBJECTIVE: To evaluate the sensitivity and specificity of ECOFAST as a diagnostic method for patients with Dengue at the Loreto Regional Hospital 2023. MATERIALS AND METHODS: A quantitative cross-sectional study with a correlational approach will be carried out. Ultrasound findings specified will be compared as at least one finding of plasma extravasation will be considered positive. Sensitivity and specificity will be calculated using the clinical and laboratory diagnosis of the treating physician as a standard of others. Data collection will be planned prospectively based on the patient's medical records. The analysis will be performed using SPSS v25 software. CONCLUSIONS: The EcoFast method, based on ultrasound in a broad way, is a methodology that allows the evaluation of different organs with plasma extravasation as a result of Dengue.